Communicative practices in context, for a knowledge-other on technologies - Rozo Sandoval, Ana Claudia (2016)
The book Marisqueiras de Passé: Saberes e Fazeres presents itself as a methodological / epistemological strategy on the contextualized communicative practice which allows readings-others on technologies: The built process as a shellfish fisheries knowledge/expertise cartographical production −based on the dialogue of knowledge− was narrated, written and photographed by its protagonists in their interest to rescue the plural analysis of technologies, from a frame of thought able to transcend developmental approaches, inherited by modernity and positioned in the knowledge / power contemporary matrix imposed by technology. The inseparable links between culture / technology are revealed to understand the geopolitical dimension of Knowledge, showing essential links between communication practices and other forms of reflexivity.